2006
DOI: 10.1523/jneurosci.3154-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Different Effects on Recognition Memory of Perirhinal Kainate and NMDA Glutamate Receptor Antagonism: Implications for Underlying Plasticity Mechanisms

Abstract: To investigate the involvement of different types of glutamate receptors in recognition memory, selective antagonists of NMDA and kainate receptors were locally infused into the perirhinal cortex of the rat temporal lobe. Such infusion of a selective kainate receptor antagonist produced an unusual pattern of recognition memory impairment: amnesia after a short (20 min) but not a long (24 h) delay. In contrast, antagonism of perirhinal NMDA glutamate receptors by locally infused AP-5 (2-amino-5-phosphonopentano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
152
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(172 citation statements)
references
References 32 publications
17
152
0
Order By: Relevance
“…The bulk of research on synaptic plasticity within the perirhinal cortex has focussed on long-term depression (LTD) due to its possible role in recognition memory (see below and Jerusalinsky et al, 1997;Warburton et al, 2003;Wan et al, 2004;Barker et al, 2006a;Griffiths et al, 2008;Seoane et al, 2009). Ziakopoulos et al (1999) demonstrated that the perirhinal cortex could also undergo depressive synaptic plasticity; short-term depression in the form of paired-pulse depression (PPD) could be induced with a 200 ms IPI and this PPD was GABA B -dependent (Ziakopoulos et al, 2000).…”
Section: Synaptic Plasticity In the Perirhinal Cortexmentioning
confidence: 99%
See 4 more Smart Citations
“…The bulk of research on synaptic plasticity within the perirhinal cortex has focussed on long-term depression (LTD) due to its possible role in recognition memory (see below and Jerusalinsky et al, 1997;Warburton et al, 2003;Wan et al, 2004;Barker et al, 2006a;Griffiths et al, 2008;Seoane et al, 2009). Ziakopoulos et al (1999) demonstrated that the perirhinal cortex could also undergo depressive synaptic plasticity; short-term depression in the form of paired-pulse depression (PPD) could be induced with a 200 ms IPI and this PPD was GABA B -dependent (Ziakopoulos et al, 2000).…”
Section: Synaptic Plasticity In the Perirhinal Cortexmentioning
confidence: 99%
“…There is much evidence to support this claim as glutamatergic signalling, crucial for synaptic plasticity, is also required for object recognition memory (de Lima et al, 2005;Winters and Bussey, 2005b;Barker et al, 2006a;Nilsson et al, 2007;Barker and Warburton, 2008). In rats, the perirhinal administration of AP-5 (Winters and Bussey, 2005b;Barker et al, 2006a) or systemic administration of MK-801 (de Lima et al, 2005;Nilsson et al, 2007) impairs object recognition tasks performance by disrupting glutamatergic signalling via the NMDA receptor.…”
Section: Object Recognition Memorymentioning
confidence: 99%
See 3 more Smart Citations